Academic Nurse Educators’ Perceptions of Classroom Assessment Practices as Means for Quality Nursing Education - C.E Oguguo, Basil; U. Ene, Catherine.; O. Dave-Ugwu, Priscilla; I. Ezechukwu, Rosaline.; I. Okebanama, Cliff; Ukala, Geoffrey; J. Agugoesi, Oluchi; C. Ugwu, Felicia (International Journal of Psychosocial Rehabilitation, 2024)
Assessment is considered a challenging task; to this effect, in order to have an efficientclassroom assessment, an adequate understanding and mastery of assessment practices isneeded by nurse educators. Nurse Educators’ are very essential in implementing the rightassessment approaches since they possess the necessary assessment practices such as theirattitudes, values, and beliefs etc. The study sought to gain an understanding of the extent towhich Nurse Educators’ use different classroom assessment tools to understand and supportboth the teaching and learning processes in undergraduate studies. Descriptive survey researchdesign was employed and 397 Nurse Educators participated in the study. The instrument usedfor data collection was ‘Bloom’s Cognitive, Affective, and PsychomotorBehavioursQuestionnaire’ (BCAPBQ) with 43-items. The internal consistency of the instrumentwas determined using Cronbach’s Alpha and the reliability index of 0.81 was obtained. Thestudy discovered thatnurse educators to higher extent perceived the levels of behaviouralobjectives as means for providing quality nursing education. The findings also showed theextentnurse educators’ assessment practices measure each levels of Bloom’s Taxonomybehaviours.The findings support previous findings of authors who found that teachers’perceptions of classroom assessment affected their classroom assessment practices.The findingsof this study will lead to a broader scale with the basic data it supplies. It will expose the nurse  educators to different strategies used in monitoring undergraduate students’ nurses learning.The research supplies good idea of the instruments for measuring those staked learningoutcomes in nursing education.